Human and society and Knowledge In Malik bin Nabi's educational thought - guendouz, mounir; Amine, ahmed (Journal of Social Sciences and Humanities, 2021)
Malik bin Nabi is one of the thinkers who attached great importance to the concept of social education Which he covered in his writings in his many books, and he singled out a special one for him when he treated it in some detail in his book "The Birth of Society". I consider it the essence upon which society is founded and by which its existence continues and lasts, it represents that space of embodiment of those spiritual values that establish the existence of historical society It is also concerned with the formation of the human being and preparing him psychologically, morally and socially in order to face the reality determinations on the one hand and build a developed and strong nation on the other hand.All this in an ethical and aesthetic framework that draws its fundamentals from the teachings of the Islamic religion and its laws.